Amyloid deposits show complexity and intimate spatial relationship with dendrosomatic plasma membranes: An electron microscopic 3D reconstruction analysis in 3xTg-AD mice and aged canines - Paworn Nuntagij (2018)
Little is known about how amyloid-β (Aβ) is deposited in relation to the complex ultrastructure of the brain. Here we combined serial section immunoelectron microscopy with 3D reconstruction to elucidate the spatial relationship between Aβ deposits and ultrastructurally identified cellular compartments. The analysis was performed in a transgenic mouse model with mutant presenilin-1, and mutant amyloid-β protein precursor (AβPP) and tau transgenes (3xTg-AD mice) and in aged dogs that develop Aβ plaques spontaneously. Reconstructions based on serial ultrathin sections of hippocampus (mice) or neocortex (dogs) that had been immunolabeled with Aβ (Aβ1-42) antibodies showed that the organization of extracellular Aβ deposits is more complex than anticipated from light microscopic analyses. In both species, deposits were tightly associated with plasma membranes of pyramidal cell bodies and major dendrites. The deposits typically consisted of thin sheets as well as slender tendrils that climbed along the large caliber dendritic stems of pyramidal neurons. No preferential association was observed between Aβ deposits and thin dendritic branches or spines, nor was there any evidence of preferential accumulation of Aβ around synaptic contacts or glial processes. Our data suggest that plaque formation is a precisely orchestrated process that involves specialized domains of dendrosomatic plasma membranes. © 2009 - IOS Press and the authors. All rights reserved.